Redox environment inducing strategy for enhancing biological phosphorus removal in a full-scale municipal wastewater treatment plant. (20th November 2022) - Hei, Shengqiang; Xu, Hui; Liu, Yanchen; Liu, Biming; Zhang, Shuo; Zhu, Xianzheng; Lin, Weichen; Chen, Lu; Jiang, Haisha; Cheng, Xianwei; Yong, Xiaolei; Wu, Xiaoyi; et al.
Abstract: Phosphorus removal from wastewater is crucial for limiting water eutrophication. However, due to improper operating conditions, tremendous phosphorus removal chemicals addition or low C/N ratio in the influent, biological phosphorus removal (BPR) has been regarded as a difficult issue in real full-scale municipal wastewater treatment plants (WWTPs), especially in the membrane bioreactor (MBR) plants with long sludge retention time. Therefore, application of effective enhanced biological phosphorus removal (EBPR) technologies in WWTPs is of great significance to improve the BPR efficiency, reduce chemicals consumption and operating cost. Favorable redox environment, characterized by ORP is important for the growth and enrichment of phosphate-accumulating organisms (PAO), which is mainly responsible for BPR. In this study, a redox environment inducing strategy for EBPR was taken in a real full-scale MBR-WWTP (treatment capacity of 2 × 10 6  m 3 /d). The results indicated that the phosphorus release and uptake rate were rather low in the biochemical tank, which reflected the low phosphate-accumulating organisms (PAO) activity and poor BPR efficiency. This problem may be due to inappropriate redox environment, inhibition by phosphorus removal chemicals or low C/N in the influent. After EBPR, the contribution percentage of BPR increased by up to 18% and chemicals dosage reduced by up to 60%. Furthermore, the relative abundance of PAO ( Dechloromonas, Thauera and OLB12 ) was significantly increased in anaerobic tank (4.62, 1.33 and 1.18%), in anoxic tank (4.85, 1.93 and 0.88%) and in oxic tank (5.17, 1.71 and 0.84%) for appropriate redox environment and relieved inhibition by less dosage of phosphorus removal chemicals. In addition, bacteria related to COD degradation and nitrogen removal were also enriched. The simultaneous enhancement of biological phosphorus removal, carbon removal and nitrogen removal was successfully realized in this research, which indicated that the strategy was effective in real large-scale WWTPs. Graphical abstract: Image 1 Highlights: Anaerobic phosphorus-release and oxic phosphorus-uptake rate of PAO was low. Chemical phosphorus removal predominated overall processes over biological removal. Recycle ratios regulation based on ORP enhanced biological phosphorus removal. Improved biological phosphorus removal resulted in reduction of PAC dosage. The relative abundance of phosphorus - accumulating bacteria increased significantly.